A Human Resource Management Model Based on Work Discipline and Supervision to Enhance Employee Career Promotion - Elfina Okto Posmaida Damanik; Risma Nurhaini Munte; Ester Mawar Siagian; Desmi Triyanti Purba (Fundamental and Applied Management Journal, 2026)
Human resource management plays a vital role in improving employee performance and career development, especially in small and medium enterprises (SMEs). This study aims to develop a human resource management model based on work discipline and supervision to enhance employee career promotion in SMEs in North Sumatra, Indonesia. A quantitative survey method was used, collecting data from employees with at least two years of work experience through purposive sampling. Data were analyzed using multiple linear regression and structural model analysis to examine relationships among variables. The findings show that work discipline positively and significantly influences career promotion, as employees with strong punctuality, responsibility, and rule compliance have better advancement opportunities. Effective supervision also significantly supports career promotion through proper guidance, monitoring, and evaluation. Simultaneously, work discipline and supervision strengthen a structured and transparent promotion system. This study contributes to a strategic HRM model that supports fair career advancement and sustainable employee development in SMEs.